Economic impact of industry-sponsored clinical trials in inflammatory bowel diseases: Results from the national institute of gastroenterology “Saverio de Bellis” - Polignano, Maurizio Gaetano; Pasculli, Giuseppe; Trisolini, Pietro; Di Lorenzo, Michele Albino; Dalfino, Giuseppe; Giannelli, Gianluigi (Frontiers in Pharmacology, 2022)
Introduction: The majority of the money spent on possible new medications’ clinical trials is accounted for by the innovative pharmaceutical sector, which also stimulates the economy of a nation. The objective of this study was to evaluate the impact of pharmaceutical industry-sponsored clinical trials (ISCTs) in inflammatory bowel diseases (IBDs) towards the national health service (NHS) in terms of avoided costs and leverage effect. Methodology: The research was conducted at National Institute of Gastroenterology, “Saverio De Bellis”, Castellana Grotte (Apulia, Italy) collecting data from profit ISCTs of pharmaceutical products conducted over the time period 2018-2020 with focus on inflammatory bowel diseases. After the quantification of health services and drug costs from the latter studies, avoided costs and leverage effects were then estimated. Results: The results on the avoided costs for healthcare facilities deriving from the conduct of clinical studies show that, in relation to the sample of five drug companies participating in our 2018-2020 analysis, out of a total of 235,102.46 €, identified as direct investment, 628,158.21 € of avoided costs for the NHS were measured, with an additional saving (leverage effect) for the NHS of 3.67 € for each € invested by the companies promoting clinical trials. Conclusion: Conducting profit clinical trials has practical benefits and a favourable macroeconomic impact that, by completing its limited resources, helps to sustain one country NHS thanks to the avoided costs while also contributing to locational and industrial policy while guaranteeing novel therapeutics and health services for the patients enrolled.